Arthroscopic Excision of Metaphyseal Distal Femoral Osteochondromas - Fabien Meta, M.D.; Sean C. Clark, M.S.; Cory G. Couch, M.D.; Aaron J. Krych, M.D.; Mario Hevesi, M.D., Ph.D. (Arthroscopy Techniques)
Osteochondromas are benign bone tumors that result in an osseous projection along with a hyaline cartilage cap that most commonly form around the knee. Typically, they are asymptomatic, however with continued growth, symptoms may arise such as pain, mechanical symptoms, or neurovascular compression due to contact with neighboring structures resulting in the need for surgical management. The presented arthroscopic technique described herein is a safe, effective, and reproducible method for excision of benign, metaphyseal, distal femoral osteochondromas.